Physics of the Earth's Interior - Barbara Romanowicz (Collège de France, 2013)
Earthquakes, tsunamis, volcanic eruptions: the extent of certain recent natural disasters and their dramatic consequences have reminded us of the power of terrestrial phenomena and of the need for scientific research to understand the Earth's dynamics more fully. Over the last twenty years the study of the Earth's interior has witnessed a real revolution, owing in particular to the development of increasingly sophisticated seismic tomography techniques and the powerful computations made possi...